Are Beijing and Shanghai automobile dependent cities? - Gao, Yuan; Newman, Peter (Edward Elgar Publishing, 2020)
Automobile dependence was a deliberate policy of many developed cities in the modernist period since the 1940s. As cities are now overcoming automobile dependence the attention has turned to the emerging world, especially China. The chapter shows that the two most influential Chinese cities, Beijing and Shanghai, have reached ‘peak car' and have low automobile dependence. The chapter suggests that although China is in a period of rapid urbanization and motorization, these two cities are not automobile dependent and are unlikely to succumb to automobile dependence. This phenomenon can be explained by economic, cultural and administrative factors, especially Chinese traditional dense urbanism, which involves mostly walking and transit urban fabrics.